HUBUNGAN ANTARA PENGETAHUAN DENGAN SIKAP REMAJA TENTANG HUBUNGAN SEKS BEBAS DI SMA NEGERI 2 KUPANG TAHUN 2014 - BOIMAU, ADRIANA M. S. (MIDWIFERY MEDICAL JOURNAL, 2014)
Background: Adolescenceis a period of timeindividualsswitchingfromphasetophasedewasa.Dimanachildatthistimeteensbeginto feelclearlyincreasedsex drivesothey aretrying to find moreinformation aboutseks.Olehdue to lackof knowledge, most teenagersmisconceptionaboutsexandtendtobenegativetoward sexbebas. Berdasarkan research dataIndonesian Family Planning Association(2001), from2479respondents aged15-24 yearsgained16.64% (227 people) said they hadsexual intercourseoutside marriage.Objective:This studyaims to determinehowthe relationshipbetweenadolescentknowledgeandattitudesaboutsexteenfree.Methods:The studiesusingcross-sectional designwithobservationvariableat a timewith arandomsamplingtechniqueandusedinstrumentis a questionnairewithclosed-ended type.Results of research: according to the results of research conducted at SMAN 2 Kupang class III with large samples of 50, from a population of 253. In getting that 47 respondents (94%) very well knowledgeable and 1 respondent (1%) 1 cukupdan knowledgeable respondents (2%) of them being negative .Berdasarkan Chi-square calculation results obtained calculated value (49.00) is greater than X2 table (3.84) which means that Ho is rejected. As for the source of sex information from 50 respondents, all of them (90%) to get information about sex from school through the lessons at school.Conclusions: The conclusions that can be that there is a relationship between knowledge and attitudes of adolescents about sex, the less knowledge of adolescents about sex more negative attitude.